Preparation and Evaluation of Midazolam Rectal Gel in vitro and in vivo - Chen, Xiaojia; Li, Wanqin; Li, Ying; Guo, Fei; Zhang, Hui; Gao, Jing; Sun, Jianxu; Zheng, Aiping (Drug Research, 2018)
Midazolam has been successfully used for sedation, which the tablets, injections and oral solutions were available in market. However, the oral bioavailability of midazolam is less due to the first effect, while injection formulation has a low patient compliance. The purpose of this study was to obtain midazolam rectal gel to meet the production and market requirements. We evaluated the in vitro release behavior of midazolam powder, a physical mixture of midazolam and HPMC, and midazolam gel. The results showed that the midazolam gel has superior release degree compared to the other. Correspondingly, midazolam gel produced relevant plasma concentrations result in the rats. At the same dose (1 mg/kg), the Cmax and AUC (0-t) of midazolam after administration of the midazolam rectal gel were 8-10 times higher than that of the oral solution. The midazolam rectal gel was evaluated for physico-chemical tests including pH, viscosity, drug content at 40°C /75%RH (relative humidity) for 180 days (6 months). It provides information about the shelf lives of medicine, as well as the conditions for their storage. Rectum irritation test demonstrated that frequent application of midazolam rectal gel did not induce rectal mucosal damage. In conclusion, midazolam rectal gel was a potential new dosage form, which could alleviate the feeling of alien, discomfort and refusal during application of the patients. It was likely to be a more convenient and effective sedative medicine form specifically for infants and children.
Keywords: midazolam; rectal gel; in vitro release; pharmacokinetic; rectal irritation